Effects of Father Absence on Childrenâs Academic Performance - Alay Ahmad, Muhammad Saifullah Qureshi (Journal of Educational, Health and Community Psychology, 2014)
AbstractÂ Â Historically father has been viewed as presented in a variety of different images to describe the script that they have been fulfilling. They have variously been presented as, normal observer, breadwinner, sex role model, and nurturing. The death of parents is one of the most severe trauma that a child can suffer. The loss of parents causes so many problems that a deprived child faces, among those problems the important problem is the effects on academic performance of children. This research study explain how father absence affect the academic performance of children, for this purpose a sample of 45 subjects is selected from population of same socioeconomic status, with no cultural differences. All the subjects were the students of 6th, 7th, 8th, 9th, and 10th grade. The subjects were selected from three types of families, intact father children, died father children and divorced father children and was kept in three groups as: present father group, died father group and divorced father group. The statistical analysis of the results by applying statistical treatment test with critical region =1.4, and significance level =0.10 show that intact father children show better academic performance than absent father children. The dyed father children and divorceeâs children show the same academic performance which reveals that father presence play a very significant role in the academic performance of children. The implication of the study will be discussed further.Â Keyword: Academic performance, father presence, and absent father.